Analysis of selected diploid banana genotypes for resistance to weevil damage and pollen quantity as key elements of banana breeding - Kemigisa, Juliet; Arinaitwe, Ivan Kabiita; Kubiriba, Jerome; Tugume, Arthur K; Tumuhimbise, Robooni (Frontiers in Plant Science, 2025)
Banana weevils (Cosmopolites sordidus) cause significant reductions in banana productivity in Uganda. Their distribution extends countrywide, with higher concentrations in the central region due to favorable environmental conditions. Integrated weevil management practices incorporate resistance into susceptible genotypes through breeding, which utilizes pollen from resistant diploid bananas. Field and pot screening experiments were conducted in central Uganda (Kawanda) to assess the response of nine outsourced diploid banana genotypes from the International Musa Transit Centre (ITC) to weevil damage. Pollen quantity of the bananas was also evaluated. The percentage of weevil damage on the peripheral and cross sections of the corms was recorded. Pollen quantity was scored on a scale of 0 to 4, with 0 representing no pollen and 4 the highest pollen production. Results showed that the genotypes Saing hil, Pisang gigi buaya, Pisang rotan, Pisang tunjuk, Morong princessa, Morong datu, and Gabah gabah were resistant to weevil damage compared to the susceptible genotypes Nakitembe and Kibuzi (EAHB). Saing hil and SH-3142 exhibited higher pollen quantities of 3.4 and 3.0, respectively, which were closest to the value of 4 observed in ‘Calcutta 4’, the most male-fertile wild diploid. Saing hil combined high resistance to weevil damage with high pollen quantity and is therefore recommended for use in conventional banana breeding.